Solusi Persamaan Difusi Adveksi Dengan Metode Pemisahan Variabel - Ihsan, Hisyam; Rustam, Ilmi Nurfaizah (Jurusan Matematika FMIPA UNM, 2022)
This research is pure research in the form of a theoretical study of the solution of advection-diffusion using separation of variable method. The purpose of this study was to determine the derivation of the advection-diffusion equation, find a solution to the advection-diffusion equation using the separation of variable method and perform simulations. Solutions of the equation using Matlab Software. The Advection Diffusion Equation is obtained from the derivation by Fick's Law. The solution of the advection-diffusion equation is by applying the separation of variable method, determining boundary conditions, separating variables, obtaining general solutions, and obtaining special solutions. Where the specific solution will be simulated.